“Effects of Medroxy Progesterone Acetate (Inject-Able Contraceptive) on Diameter of Graffian Follicle (Ovary) of Adult Albino Rats” - Soofia Nigar, Hira Ahmed, Hina Jabeen, Shazia Fahmi, Raffat Rasool, Amna Mughal (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: An injectable birth control called Medroxy Progesterone Acetate (MPA) was used in the study to see how it affects adult female albino rats’ ovaries. Study design An experimental study Place of study : To conduct the research, scientists worked with animals at the Dow University of Health Sciences’ Animal House, the Institute of Basic Medical Sciences, and the Dow Diagnostic Research and Reference Laboratory (DDRRL). In the months of April and July of 2012, researchers conducted their investigation. Materials and Method:For the purpose of the research, a total of 72 female albino rats were chosen and divided into three distinct categories. Each group was further subdivided into three smaller groups based on the length of time that the therapy session lasted. The experiment utilized a group size of n = 24, which served as the control. The dose of MPA that was given to Group B (which consisted of 24 people) was 3 mg/kg of body weight. Participants in Group C (n = 24) were given an MPA dose that was two times higher than those in Group A (3 mg/kg). A single injection of MPA was given to group B as well as group C at the beginning of the experiment. During the course of the research, it was noticed that the ovaries of the animals had changed both in terms of their shape and their structure. Hematoxylin, eosin, and masson’s trichrome were the stains that were used to color the tissues of the ovary. With the assistance of an ocular and stage micrometer, even minute differences could be detected and measured. The Kruskal-Wallis test and Tukey’s test are two examples of nonparametric statistical analysis that were used to investigate the differences in each group’s variables. Result: In comparison to control groups, experimental animals fed MPA had significantly smaller diameters of graafian follicles (DOF) than animals in the control groups. There was a significant difference in depth-of-field (DOF) between groups A1, B1, and C1 after one month of treatment. Groups A2, B2, and C2 each had a DOF of 571.25 98.26 meters, 288.25 100.80 meters, and 179.0 37.23 meters. In groups A3, B3, and C3, the DOF ranged from 699.75 m to 128.7 m, 230.37 m to 20.83 m, and 159.37 m to 47.65 m. Conclusion: Research shows that MPA can lower the amount of follicular atresia as well as chronic anovulation, according to the findings of this study. With this study’s findings, we can better understand the risks that hormonal contraceptives like injections have to women’s health.